Proceedings of the Workshop on INTelligent Embedded Systems Architectures and Applications 2018
DOI: 10.1145/3285017.3285024
|View full text |Cite
|
Sign up to set email alerts
|

Towards plug&play smart thermostats inspired by reinforcement learning

Abstract: Buildings are immensely energy-demanding and this fact is enhanced by the expectation of even more increment of energy consumption in the future. In order to mitigate this problem, a lowcost, flexible and high-quality Decision-Making Mechanism for supporting the tasks of a Smart Thermostat is proposed. Energy efficiency and thermal comfort are the two primary quantities regarding control performance of a building's HVAC system. Apart from demonstrating a conflicting relationship, they depend not only on the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In addition to penalizing temperature deviations from a setpoint, frequent switching of the on/off heating element can be penalized if it is perceived as annoying to the occupant, due to the noise involved, for example [88]. An alternative approach to binary control is to allow the RL agent to add or subtract a fixed value from the temperature setpoint [89][90][91]. A double binary control approach involves all the possible combinations of on/off control of two heating elements in a hot water tank [92].…”
Section: Overview Of the Analyzed Articlesmentioning
confidence: 99%
“…In addition to penalizing temperature deviations from a setpoint, frequent switching of the on/off heating element can be penalized if it is perceived as annoying to the occupant, due to the noise involved, for example [88]. An alternative approach to binary control is to allow the RL agent to add or subtract a fixed value from the temperature setpoint [89][90][91]. A double binary control approach involves all the possible combinations of on/off control of two heating elements in a hot water tank [92].…”
Section: Overview Of the Analyzed Articlesmentioning
confidence: 99%
“…An online version of FQI that uses a neural network, Neural Fitted Q-Iteration, was proposed by [26]. Marantos et al [27] applied NFQ batch RL to control the thermostat set-point of a single-zone building where input state was fourdimensional (outdoor and indoor temperatures, solar radiance, and indoor humidity) and action was one-dimensional with three discrete values.…”
Section: Rl With Action-value Function Approximationmentioning
confidence: 99%
“…The authors reported energy savings in the range of 4 -11%, comparable to the previous study. [70]. This approach also used a neural network to approximate the Q function.…”
Section: Hvacmentioning
confidence: 99%